Recent aeroelastic investigations at the College of Aeronautics - Johns, D. J. (College of Aeronautics, 1965)
Introduction Since the College of Aeronautics was founded in 1946 aeroelasticity has been the subject of much research by both students and staff in the Departments of Aircraft Design and Aerodynamics. It is not the present intention to review the entire period since 1946, but, rather, to concentrate on the period 1958/63 during which the author has been associated with the College. In this period aeroelastic research has been concentrated on four main themes, viz: (a) panel, membrane and wing instabilities; (b) investigations associated with the Morane-Saulnier M.S.760 'Paris'; (c) investigations on Design Project Studies, and (d) helicopter problems. The list of references covers the entire period up to 1963 and contains. references dealing with such related topics as flutter model construction and unsteady aerodynamics. These are included for the cake of completeness since such investigations often bear directly on the more specific problems of aeroelasticity. It should also be mentioned that there has been considerable research on vibration testing, impact loading, etc., but such references are not included. No detailed comparisons have been attempted between the research described and similar work done elsewhere - for these the appropriate references must be studied. It must be emphasised however that the research performed whilst being certainly worthwhile for its own sake also enables the students to become familiar with research methods - a primary aim of the College.